2014
DOI: 10.1007/s00464-014-3788-z
|View full text |Cite
|
Sign up to set email alerts
|

Portomesenteric venous thrombosis following major colon and rectal surgery: incidence and risk factors

Abstract: BMI ≥ 30 kg/m(2), thrombocytosis, and restorative proctocolectomy were significant predictors of PMVT. Initial diagnostic studies showed a PMVT rate of 1.4%; however, after expert focused radiologic review, the actual rate was 3%. Thus, the diagnosis of PMVT is difficult and readmission after colorectal surgery should prompt its consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…The rates of any complication, small bowel obstruction and pouch loss/pouch failure/pouch excision reported across the 17 USA studies were higher compared with those reported across the 11 non‐USA studies (46.8%, 17.2% and 13.3% vs. 16.7%, 14.9% and 2.2% respectively). The rates of ileus, pouchitis, faecal incontinence and fistula could not be compared as they were reported in the USA studies only; similarly mortality was reported in the non‐USA studies only.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The rates of any complication, small bowel obstruction and pouch loss/pouch failure/pouch excision reported across the 17 USA studies were higher compared with those reported across the 11 non‐USA studies (46.8%, 17.2% and 13.3% vs. 16.7%, 14.9% and 2.2% respectively). The rates of ileus, pouchitis, faecal incontinence and fistula could not be compared as they were reported in the USA studies only; similarly mortality was reported in the non‐USA studies only.…”
Section: Resultsmentioning
confidence: 64%
“…Hand‐searches of conference proceedings and of reference lists yielded six additional studies. The SR update yielded three further studies . In total, 28 studies were included: 27 non‐RCTs and one RCT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Während die primäre Thrombozytose ein unumstrittener prothrombogener Risikofaktor darstellt, gilt die sekundäre Thrombozytose generell als harmlos [13]. Obwohl große prospektive Studien größtenteils fehlen, konnte in mehreren Analysen gezeigt werden, dass eine Thrombozytose in unterschiedlichen Situationen wie postoperativ [43,44], posttraumatisch [45], bei Intensivpatienten [46,47], SIRS (systemic inflammatory response syndrome) [48] [66,67]. Die Ausprägung der CED-assoziierten Thrombozytose korreliert mit der entzünd-lichen Aktivität [68,69] und ist einerseits durch die Wirkung proinflammatorischer Zytokine wie Interleukin 6 bedingt [70], andererseits scheint Eisenmangel ebenfalls eine Rolle zu spielen [21,69,71].…”
unclassified